Propuesta de mejora al proceso de Evaluación Docente de la ESPAM MFL - Lucas Vera, Dolores Carolina (2017)
This article presents the main results of research aimed at improving the teacher evaluation process. The objective of the research was to propose improvements to the teaching evaluation process at the Higher Polytechnic School of Agriculture of Manabí Manuel Félix López, for which it was necessary to use the AS IS technique, which allowed to obtain the respective flow, description and responsible for each one of the activities that make up each subprocess, after that the analysis matrix methodology of added-value was applied, which allowed to identify the activities that do not add value to the process, the same ones that must be eliminated or improved. Once the added-value analysis matrix was applied, it was identified that the planning sub process was the only efficient thread, while the key threads to be improved are; execution, results, appeal and publication. The identification of failures in the four subprocesses studied led to the creation of new flows, implementing or reducing activities that allow members of General Evaluation Coordination to obtain an efficient and effective process. The changes and improvements to the subprocesses are due to the technological and educational advances that are being presented at the moment, forcing those in charge of processing information in institutions of higher education, transform and modernize the manual processes to digital processes because the current higher education system demands speed, efficiency and excellence in the development of processes and procedures